2015
DOI: 10.3892/etm.2015.2762
|View full text |Cite
|
Sign up to set email alerts
|

Hedyotis diffusa Willd overcomes 5-fluorouracil resistance in human colorectal cancer HCT-8/5-FU cells by downregulating the expression of P-glycoprotein and ATP-binding casette subfamily G member 2

Abstract: Abstract. Previous studies have demonstrated thatHedyotis diffusa Willd (HDW), a traditional Chinese herbal medicine, exhibits potent anticancer activity in models of colorectal cancer (CRC). Aggressive forms of CRC exhibit resistance to widely used chemotherapeutic drugs, including the antimetabolite, 5-fluorouracil (5-FU); however, less is known with regard to the activity of HDW against 5-FU-resistant cancer. In the present study, the mechanism of action and the potency of ethanol extracts of HDW (EEHDW) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…Meanwhile, the ethanolic extract of H. diffusa displayed an inhibition effect on CT-26 cells with inhibitory rates from 35.46%˘3.59% to 71.84%˘3.12% at different concentrations (0.06 mg/mL, 0.08 mg/mL, 0.10 mg/mL, 0.12 mg/mL, 0.14 mg/mL, 0.16 mg/mL, 0.18 mg/mL and 0.20 mg/mL) and showed a stronger inhibition effect with an increase of concentration [60]. Li et al [61] revealed that the ethanolic extract treatment could overcome 5-fluorouracil resistance in HCT-8/5-FU cells by downregulating the expression of P-gp and ABCG2. In addition, 2-hydroxymethy-1-hydroxy anthraquinone (IC 50 45 ”M) and ursolic acid (IC 50 71 ”M)) isolated from H. diffusa exhibited inhibition effects on Caco-2 cell proliferation [5], and the mechanism of the inhibition effect for ursolic acid might include the cleavage of the Poly (ADP-ribose) Polymerase (PARP) [62].…”
Section: Anti-colorectal Cancer Activitymentioning
confidence: 99%
“…Meanwhile, the ethanolic extract of H. diffusa displayed an inhibition effect on CT-26 cells with inhibitory rates from 35.46%˘3.59% to 71.84%˘3.12% at different concentrations (0.06 mg/mL, 0.08 mg/mL, 0.10 mg/mL, 0.12 mg/mL, 0.14 mg/mL, 0.16 mg/mL, 0.18 mg/mL and 0.20 mg/mL) and showed a stronger inhibition effect with an increase of concentration [60]. Li et al [61] revealed that the ethanolic extract treatment could overcome 5-fluorouracil resistance in HCT-8/5-FU cells by downregulating the expression of P-gp and ABCG2. In addition, 2-hydroxymethy-1-hydroxy anthraquinone (IC 50 45 ”M) and ursolic acid (IC 50 71 ”M)) isolated from H. diffusa exhibited inhibition effects on Caco-2 cell proliferation [5], and the mechanism of the inhibition effect for ursolic acid might include the cleavage of the Poly (ADP-ribose) Polymerase (PARP) [62].…”
Section: Anti-colorectal Cancer Activitymentioning
confidence: 99%
“…HDW is used as a cancer therapy agent, which reduces the adverse reactions of chemotherapy (12). Several reports have demonstrated that the extract of HDW exerts its therapeutic effects by inducing mitochondrial apoptosis in numerous human cancer cell lines (13–15).…”
Section: Introductionmentioning
confidence: 99%
“…HDW has also been widely used as an important component in traditional Chinese medicine (TCM) prescription formulae for the treatment of various types of cancer, including CRC (17)(18)(19). Our previous studies have demonstrated that HDW is able to inhibit colon cancer growth in vivo and in vitro by promoting apoptosis of cancer cells, inhibiting proliferation, tumor angiogenesis and MDR reversal (20)(21)(22)(23)(24)(25). However, the precise mechanism of the in vivo anti-cancer activity of HDW remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%